2007
DOI: 10.2527/jas.2006-511
|View full text |Cite
|
Sign up to set email alerts
|

Contractile protein content reflects myosin heavy-chain isoform gene expression1

Abstract: Muscle fiber types are classified based on contractile speed and type of metabolism. Fast-contracting fibers involve mainly glycolytic-based metabolism, whereas slow-contracting fibers involve a more oxidative type of energy metabolism. The relationship between expression of the genes controlling these functional characteristics and their relative protein abundance in porcine muscle is unknown. The objective of this study was to determine the expression of adult myosin heavy-chain (MyHC) genes and their corres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 28 publications
(27 reference statements)
1
20
0
1
Order By: Relevance
“…Hemmings et al (2009) found a high expression of myosin IIB isoform in STM of sheep, but not in LDM. In contrast, Gunawan et al (2007) reported that myosin IIB expression was higher in LDM of pigs, as compared to STM. Brodsky et al (2004) concluded that protein deprivation in humans reduces the expression of fast twitch myosin heavy chain and that dietary amino acid scarcity produces a change in myosin isoform distribution via posttranscriptional mechanisms.…”
Section: Discussionmentioning
confidence: 86%
“…Hemmings et al (2009) found a high expression of myosin IIB isoform in STM of sheep, but not in LDM. In contrast, Gunawan et al (2007) reported that myosin IIB expression was higher in LDM of pigs, as compared to STM. Brodsky et al (2004) concluded that protein deprivation in humans reduces the expression of fast twitch myosin heavy chain and that dietary amino acid scarcity produces a change in myosin isoform distribution via posttranscriptional mechanisms.…”
Section: Discussionmentioning
confidence: 86%
“…According to Lefaucheur et al (2002), type IIB fibers, which account for approximately 80% of the total fibers in some pig muscles, are extensively expressed in the ST and LD of pigs. Gunawan et al (2007) reported higher expression of myosin IIB isoform in the LD compared with the ST in pigs. In this study, myosin was expressed in both muscles, but the expression in LD was approximately 6-fold higher compared to that in ST.…”
Section: Discussionmentioning
confidence: 93%
“…The diaphragm is comprised mainly of oxidative type I and type IIa fibres, where the SM has 86-88% type II fibres, with the majority of these being the fast glycolytic IIb type. [26][27][28] It has previously been shown that the myogenic behaviour of satellite cells isolated from muscle with contrasting fibre type composition, exhibit differences in proliferation and fusion rates. 29 Our findings support those of Bajot et al, 29 in that satellite cells from predominantly slow muscle types appear superior at myogenic differentiation in vitro.…”
Section: Discussionmentioning
confidence: 99%